Abilities of geoinformational systems for functional zoning of conservation areas (on the example of NNP «Homelshansky lisi») - ВОЛКОВ, А. І.; ПОПИК, О. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy)
The research concerns approach to functional zoning of conservation areas and designing appropriate database using geographical informational technologies. The approach was applied to improve functional zoning of National Natural Park «Homelshansky Lisi». The main feature of the approach is considering level of anthropogenic load on the environment.